Heme-heme oxygenase-2 reduces the atherosclerosis by preventing inflammation - Zhenzhen Wang; Xiaoqiang Zhan; Shuai Yang; Yang Chen; Yingchao Bi; Xuemei Xian; Quangang Chen; Xufeng Han; Zhangping Yang; Renjin Chen (Elsevier, 2023)
Objective: Heme oxygenase (HO) has been shown to have important antioxidant and anti-inflammatory properties, resulting in a vascular antitherogenic effect. This study was undertaken to evaluate the role of HO-2 in atherosclerosis. Method and results: The expression levels of HO-2 were evaluated in M1 and M2 bone marrow macrophage induced by LPS and IL4. The expression of HO-2 was significantly higher in M2 macrophage than in M1 macrophage. Western diet (WD) caused a significant increase in HO-2 expression in ApoE−/− mice. The adeno-associated viral (AAV) vectors expressing HO-2 was constructed, and the mice were received saline (ApoE−/−), AAV (ApoE−/−), AAV-HO-2 (ApoE−/−) on WD at 12 weeks and their plasma lipids, inﬂammatory cytokines, atherosclerosis were evaluated for 16 weeks. The results showed AAV-HO-2 was robust, with a significant decrease in the en face aortas, lipids levels, inﬂammatory cytokines and M1 macrophage content in AAV-HO-2 ApoE−/− compared to control AAV-ApoE−/−. Conclusion: HO-2 expression in macrophages plays an important role of the antiatherogenic effect, decreasing the inflammatory component of atherosclerotic lesions. These results suggest that HO-2 may be a novel therapeutic target for cardiovascular diseases.